Microscophy Identification of Toxocara cati First Stage Larvae and Second Stage Larvae - Eny Coolfina Simarmata; Kusnoto Kusnoto; Mochamad Lazuardi; Setiawan Koesdarto; Endang Suprihati; Kuncoro Puguh Santoso (Journal of Parasite Science (JoPS), 2019)
This study was aimed to identify the ultra structural morphology of Toxocara cati First Stage Larvae and Second Stage Larvae using Light Microscope. Toxocara cati larvae were obtained from adult worm eggs then were treated in phospat buffer saline with comparasion 1 : 1 until it reached the stage of larvae 1 and 2. The shell of egg Toxocara cati were thick and usually consist of three layers. The first layer was inner membrane, the second layer was middle layer and the third was outer layer. The results of larvae morphology that were identified using light microscope showed that the anterior part of Toxocara cati first stage larvae has a dorsal lip and esophagus and intestine on the posterior part but it could not be identified perfectly. The anterior part of Toxocara cati second stage larvae that were identified has three lips that leads directly into the oesophagus. Three lips on the anterior part of Toxocara cati larvae 2 consist of a dorsal lip and two subventral lips. Morphological of Toxocara cati larvae similar with the Toxocara cati adult worms because morphology of larvae and adult stage was difficult to differentiated.